If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P * 2x = 2 * 4 * 2x Reorder the terms for easier multiplication: 2P * x = 2 * 4 * 2x Multiply P * x 2xP = 2 * 4 * 2x Multiply 2 * 4 2xP = 8 * 2x Multiply 8 * 2 2xP = 16x Solving 2xP = 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -16x + 2xP = 16x + -16x Combine like terms: 16x + -16x = 0 -16x + 2xP = 0 Factor out the Greatest Common Factor (GCF), '2x'. 2x(-8 + P) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-8 + P)' equal to zero and attempt to solve: Simplifying -8 + P = 0 Solving -8 + P = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + P = 0 + 8 Combine like terms: -8 + 8 = 0 0 + P = 0 + 8 P = 0 + 8 Combine like terms: 0 + 8 = 8 P = 8 Add '-1P' to each side of the equation. P + -1P = 8 + -1P Combine like terms: P + -1P = 0 0 = 8 + -1P Simplifying 0 = 8 + -1P The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 1.25+.66q= | | -33-[2+5y-7(y-2)]=-11(2y-5)-[5(y-1)-3y+3] | | 3x^2+12x=-26 | | 4(x-1)-2(x+5)=32 | | sqrt(4z+9)=z+1 | | 8z^3-12z^2+10z-3=0 | | 7x-(8x+8)=x-9 | | 10-3q=1 | | 4(2+3x)=5 | | h=-64t^2+qt+k | | 392*x=49 | | 69x=690 | | 40x+34=634 | | 2x+32=7x+7 | | x(2x+21)=180 | | p(x)=x^2-7x-10 | | x^2+a^2-14x-10a+58=0 | | 4(x-1)+13=x-3(x+1) | | 5+2y=15-3y | | G=9/4(p-1) | | 30=5c+20 | | 15-27b+11=-244 | | 46+X=349 | | 5x-1=2x-5 | | LOG(7)(4-X)=1 | | 3x-14+3x=3+6x-17 | | 15a^2-6ab-8a^2+20-5ab-31+a^2-ab=0 | | LOG(7)4-X=1 | | 10x=9x+21 | | 9y^2+24y+72x+16=0 | | (.2x)+x=40 | | 45x=64x+8 |